Nationalism and the Cohesive Society: A Multilevel Analysis of the Interplay Among Diversity, National Identity, and Social Capital Across 27 European Societies. (February 2013) - Reeskens, Tim; Wright, Matthew
A spate of work has demonstrated tensions between ethno-cultural diversity and social capital. Some have suggested that attachment to the nation can foster cross-group trust, particularly if this national self-definition is "civic" in character rather than "ethnic" (the Miller thesis). Similarly, others have argued that civic nations are less likely to suffer reduced social capital in response to increased diversity, as the sense of threat that typically emerges in ethnically diverse contexts will be mitigated (the Putnam thesis). The authors test these hypotheses on 27 countries using both contextual-level data and the latest wave of the European Values Study (2008). Though the evidence is mixed on civic nationalism, the authors find strong evidence that ethnic nationalism goes hand-in-hand with reduced social capital and that it increases the negative social impact of diversity. So although this study only partially confirms the benefits of civic nationalism, it clearly underlines the costs of its ethnic variety.